Case report and literature review of rezvilutamide in the treatment of hormone-sensitive prostate cancer - Zhang, Chunlei; Ren, Jie; Kang, Yindong; Chang, Dehui (Frontiers in Oncology, 2024)
Background: Prostate cancer represents a major health concern worldwide, with the treatment of metastatic hormone-sensitive prostate cancer (mHSPC) and locally advanced prostate cancer posing a particular challenge. Rezvilutamide, a new androgen receptor antagonist from China, has shown early promise; however, its real-world effectiveness and safety profile require further evidence. This case series evaluates the preliminary clinical outcomes of rezvilutamide in combination with androgen deprivation therapy (ADT), focusing on PSA response and radiological findings across various stages of prostate cancer in four patients. Case Description: Case 1 details a 68-year-old male with low-volume mHSPC who exhibited a positive therapeutic response, demonstrated by decreasing PSA levels and improved radiographic results, despite experiencing mild side effects related to the drug. Case 2 describes a 71-year-old male with high-volume mHSPC who had a favorable outcome, with no significant changes in tumor size or metastatic spread and no negative reactions to the drug. Case 3 involves a 55-year-old male with locally advanced prostate cancer, who saw a reduction in PSA levels and a small decrease in tumor volume, yet with ongoing bladder involvement. Genetic testing showed no significant mutations. Case 4 presents a 74-year-old male with extensive metastatic disease who initially responded to the treatment but later exhibited disease advancement and an ATM gene mutation, signaling a shift to metastatic castration-resistant prostate cancer (mCRPC). This finding underscores the crucial role of genetic testing in directing future treatment, with therapies such as olaparib or chemotherapy being advised. Conclusion: Rezvilutamide has shown a potential benefit in the management of mHSPC and locally advanced prostate cancer, generally with a mild safety profile. Initial positive responses, particularly in PSA decline and radiographic progression, are promising. Nevertheless, the varying responses, notably concerning genetic mutations, highlight the necessity for tailored treatment approaches. Due to the small cohort and brief follow-up period, more extensive research with larger populations and prolonged monitoring is essential to conclusively determine the benefits and safety of rezvilutamide. The utilization of genetic insights is key to refining treatment decisions and enhancing outcomes for patients with advanced prostate cancer.